Physiotherapists may stigmatise or feel unprepared to treat people with low back pain and psychosocial factors that influence recovery: A systematic review - Synnott, A.; O'Keeffe, M.; Bunzli, Samantha; Dankaerts, W.; O'Sullivan, Peter; O'Sullivan, K. (Australian Physiotherapy Association, 2015)
Question: What are physiotherapists' perceptions about identifying and managing the cognitive, psychological and social factors that may act as barriers to recovery for people with low back pain (LBP)? Design: Systematic review and qualitative metasynthesis of qualitative studies in which physiotherapists were questioned, using focus groups or semi-structured interviews, about identifying and managing cognitive, psychological and social factors in people with LBP. Participants: Qualified physiotherapists with experience in treating patients with LBP. Outcome measures: Studies were synthesised in narrative format and thematic analysis was used to provide a collective insight into the physiotherapists' perceptions. Results: Three main themes emerged: physiotherapists only partially recognised cognitive, psychological and social factors in LBP, with most discussion around factors such as family, work and unhelpful patient expectations; some physiotherapists stigmatised patients with LBP as demanding, attention-seeking and poorly motivated when they presented with behaviours suggestive of these factors; and physiotherapists questioned the relevance of screening for these factors because they were perceived to extend beyond their scope of practice, with many feeling under-skilled in addressing them. Conclusion: Physiotherapists partially recognised cognitive, psychological and social factors in people with LBP. Physiotherapists expressed a preference for dealing with the more mechanical aspects of LBP, and some stigmatised the behaviours suggestive of cognitive, psychological and social contributions to LBP. Physiotherapists perceived that neither their initial training, nor currently available professional development training, instilled them with the requisite skills and confidence to successfully address and treat the multidimensional pain presentations seen in LBP. Registration: CRD 42014009964.